Performance of the Early Access AmpliSeq™ Mitochondrial Panel with degraded DNA samples using the Ion Torrent™ platform. Issue 21 (30th January 2018) - Wai, Ka Tak; Barash, Mark; Gunn, Peter
Abstract: The Early Access AmpliSeq™ Mitochondrial Panel amplifies whole mitochondrial genomes for phylogenetic and kinship identifications, using Ion Torrent™ technology. There is currently limited information on its performance with degraded DNA, a common occurrence in forensic samples. This study evaluated the performance of the Panel with DNA samples degraded in vitro, to mimic conditions commonly found in forensic investigations. Purified DNA from five individuals was heat‐treated at five time points each (125°C for 0, 30, 60, 120, and 240 min; total n = 25). The quality of DNA was assessed via a real‐time DNA assay of genomic DNA and prepared for massively parallel sequencing on the Ion Torrent™ platform. Mitochondrial sequences were obtained for all samples and had an amplicon coverage averaging between 66X to 2803X. Most amplicons (157/162) displayed high coverages (452 ± 333X), while reads with less than 100X coverage were recorded in five amplicons only (90 ± 5X). Amplicon coverage was decreased with prolonged heating. At 72% strand balance, reads were well balanced between forward and reverse strands. Using a coverage threshold of ten reads per SNP, complete sequences were recovered in all samples and resolved kinship and, haplogroup relations. Additionally, the HV1 and HV2 regions of the reference and 240‐min heat‐treated samples ( n = 10) were Sanger‐sequenced for concordance. Overall, this study demonstrates the efficacy of a novel forensic Panel that recovers high quality mitochondrial sequences from degraded DNA samples.